Answer:
(5,2,2)
Step-by-step explanation:
-3x+4y+2z = -3
2x-4y-z=0
y = 3x-13
Multiply the second equation by 2
2*(2x-4y-z)=0*2
4x -8y -2z =0
Add this to the first equation to eliminate z
-3x+4y+2z = -3
4x -8y -2z =0
-------------------------
x -4y = -3
Take the third equation and substitute it in for y
x - 4(3x-13) = -3
Distribute the 4
x - 12x +52 = -3
Combine like terms
-11x +52 = -3
Subtract 52 from each side
-11x +52-52 = -3-52
-11x = -55
Divide by -11
-11x/-11 = -55/-11
x=5
Now we can solve for y
y =3x-13
y =3*5 -13
y = 15-13
y=2
Now we need to find z
2x-4y-z=0
2(5) -4(2) -z=0
10-8 -z=0
2-z=0
Add z to each side
2-z+z= 0+z
2=z
x=5, y=2, z=2
(5,2,2)
Answer:
R290.1
Step-by-step explanation:
Let
x = charge before he put his prices up
New charge = R320
Percentage increase in price = 7%
x + 7% of x = 320
x + 0.07 * x = 320
x + 0.07x = 320
1.07x = 320
x = 320/1.07
x = 299.06542056074
Approximately
x = R290.1
Charge before he put his prices up = R290.1
Answer:
j = 2z + 1
jennifer is one year older or jennifer is plus one.
twice zacks age or two times zacks age.
jennifer's age is two times zacks age plus one or
j = 2z + 1
Ask your teacher for help you didn't give us a lot of details at all . Sorry I could help you .